Інтелектуальні технології як могутні важелі розвитку економіки - Бондар, М. В. (НТУ "ХПІ", 2010)
Рассматриваются современные образовательные потребности общества и перспективы их решения с помощью интеллектуальных технологий, взаимосвязь и взаимообусловленность интеллектуальной культуры и профессиональной подготовки студентов экономических высших учебных заведений.

Contemporary educational problems of society are considered. Those problems can be solved with intelligent and adaptive technologies. Intercommunication and interconditionality of intellectual culture and professional preparation of students of economic higher educational establishments is considered.
Іntellectual technologies as mighty levers of development of economy
Keywords: ефективність економіки; соціально-економічний прогрес; перетворення інформації; система освіти; методи мислення; способи діяльності